Body Composition in Children: What Does It Tell Us So Far? - Odysseas Androutsos; Antonis Zampelas (MDPI AG, 2022)
The Special Issue "Body Composition in Children" of the journal "CHILDREN" aimed to publish both original and review articles focusing on the prevalence and determinants of obesity across childhood, the role of body composition in children's health, new approaches to assessing body composition, and interventions aiming to improve body composition in children and adolescents [...]